Populism and polarization in social media without fake news: The vicious circle of biases, beliefs and network homophily - Zaruhi Hakobyana; Christos Koulovatianos (Goethe University Frankfurt, Center for Financial Studies (CFS), 2019)
We build a search-and-matching algorithm of network dynamics with decision-making under incomplete information, seeking to understand the determinants of the observed gradual downgrading of expert opinion on complicated issues and the decreasing trust in science. Even without fake news, combining the internet's ease of forming networks with (a) individual biases, such as confirmation bias or assimilation bias, and (b) people's tendency to align their actions with those of peers, produces populist and polarization network dynamics. Homophily leads to actions with more weight on biases and less weight on expert opinion, and such actions lead to more homophily.
urn:nbn:de:hebis:30:3-438719
Keywords: D85; D83; D82; D72; C78; 330; network dynamics; internet; higher-order beliefs; learning; expertopinions; biased assimilation; confirmation bias